1992
DOI: 10.1007/bf01623182
|View full text |Cite
|
Sign up to set email alerts
|

Comparison and investigation of bone mineral density in opposing femora by dual-energy X-ray absorptiometry

Abstract: A dual-energy X-ray absorptiometry (DXA) machine was used to measure the bone mineral density (BMD) of both femora in 760 female volunteers. Each volunteer completed a questionnaire and exclusion criteria were applied such that only 480 of these were considered normal subjects. The remaining 280 women failed to comply with the criteria and were considered 'abnormal'; their BMD results were analysed separately. Two abnormal subgroups, one with previous long bone fractures and one with radiologically diagnosed o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
20
1

Year Published

1994
1994
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 8 publications
5
20
1
Order By: Relevance
“…The magnitude of this difference indicates a considerable risk of misclassifying bone status when only one side is measured. In accordance with previous results, left or right handedness was not related to the direction of this difference [25]. The functional division of motor tasks between the left and right hand may not apply to different use of the right and left leg.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The magnitude of this difference indicates a considerable risk of misclassifying bone status when only one side is measured. In accordance with previous results, left or right handedness was not related to the direction of this difference [25]. The functional division of motor tasks between the left and right hand may not apply to different use of the right and left leg.…”
Section: Discussionsupporting
confidence: 91%
“…The difference in BMD between contralateral bones has been the subject of investigation before, and it has been suggested that routine BMD measurements at the hip should include both sides [25]. In this study substantial differences in calcaneal ultrasound parameters between the left and the right side were measured.…”
Section: Discussionmentioning
confidence: 92%
“…Values from the non-fractured limb were used as a control for measurements. Previous studies have shown that there is no effect of lower limb dominance on DXA BMD and velocity of sound (VOS) in a normal population [20,27,28]. However, broadband ultrasound attenuation (BUA) has previously shown a difference, but this could be as a consequence of the artifact of the measurement rather than any true difference in the bone [29].…”
Section: Subjectsmentioning
confidence: 72%
“…Arguments for scanning both hips include the differences between the left and right T-scores observed in some patients who may result in the patient being classified differently if one or both hips are scanned [1][2][3][4][5], and being able to follow up patients who fracture one hip or undergo hip replacement. Arguments against scanning both hips include the good correlation that exists between the BMD of both hips [6][7][8][9][10][11], unnecessary exposure to radiation and the time taken to perform the scan. On the other hand, exposure to radiation is now so small as to be negligible, and the time factor is no longer an issue with modern densitometers, many offer the ability of scanning both hips without repositioning the patient.…”
Section: Introductionmentioning
confidence: 99%